Indonesian Teen Romanticism: The Underlying Ideology of œFilm Television (FTV) During Covid-19 Pandemic from Gender Perspective - Refti Handini Listyani; FX Sri Sadewo; Mohammad Reevany Bustami; Moh. Mudzakkir; Emy Susanti (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
This research examines the underlying ideology(s) of a TV program called ˜Film Television (FTV). This TV program is on during the Covid-19 Pandemic. Specifically, using framing analysis and gender perspective approach as a methodology, this research analyses the ways in which these ideologies developed in FTV. Six prime samples of FTV were chosen, namely Laki-laki Buaya Darat, Cowok Gue IQ-nya Ancur Banget, Cowok Gue Pendek Bener, Pacar honorer, Ganteng-ganteng Medit, Pacar Gue Brondong. The findings reveal a thrust of twin-contrarian thrust of messaging. There are two embedded ideologies underlying the FTV. First, the FTV production house carries a patriarchal ideology by raising themes that discriminate against women through stereotypes against women that appear in the story. Second, the FTV production house carries the ideology of feminism, with themes that position women as super-ordinates. Women occupy a higher social class than men. This finding of twin-contrarian ideological thrust offers an important contribution to the gender theoretical vacuum of Indonesian TV as an example of Asian teen romanticism in national TV programming during a global crisis. It has conceptual implication on the repertoire of social science knowledge, especially sociology particularly research on womens body and beauty, sociology of gender and media, and sociology of family.